DIFFERENT VERBAL DIRECTION IN SIMILAR QURANIC STORIES / THE STORY OF MOSES WITH PHARAOH AS A MODEL - Shabib, Taha Ibrahim (International Journal of Psychosocial Rehabilitation, 2020)
The Qur'anic stories occupied a large area in the Holy Qur’an. It exceeded a quarter of the Holy Qur’an, and some stories were repeated many times to show or clarify an important aspect because the Qur’anic story did not come to show or explain one goal, but that these stories have many goals and multiple objectives. This matter requires a change in some words in the context of these stories, this research comes to study the differences contained in the context of Quranic stories.